Evolution and synthesis of knowledge on an enigmatic neurological pathology : Nodding Syndrome - (:unkn) unknown (My University, 2022)
The Nodding Syndrome (NS) is an atypical form of childhood epilepsy that has been prevalent in East Africa for many years. The aim of this thesis was to provide as comprehensive an overview as possible of this condition. To achieve this objective, we first confirmed, through a field survey, the existence of NS cases in the Central African Republic, thus confirming an extension to Central Africa. Next, we conducted a systematic review of the literature which allowed us to: 1) study the contemporary geographical distribution of NS cases (which remains limited to Eastern and Central Africa); 2) identify the limitations and challenges of an inoperative definition of the condition and thus propose one that is suitable for epidemiological investigations; 3) describe the particular clinical presentations of NS; 4) identify the treatments used and their alternatives; and 5) carry out a detailed synthesis of etiological research, since its cause remains unknown. Finally, we have proposed a multicentric survey with the main objective of investigating the possible/probable etiologies of NS. This thesis has thus made it possible to measure this public health burden, which remains limited (for the time being) to sub-Saharan Africa, and to highlight the many challenges facing the scientific community in the fight against this pathology (with its unpredictable epidemiological twists and turns). By gathering and studying almost all the publications on NS up to the end of the year 2021, this work aims at providing a comprehensive view of what is known about NS today, and of the questions that remain unanswered. The epidemiological and clinical contributions may provide new directions on the subject, including helping to design area-specific public health strategies for better management of children affected by this dreadful disease.
Keywords: African Research